Amidated polyacrylic acid water-based polymer binder for silicon-based negative electrode of lithium ion battery as well as preparation method and application of amidated polyacrylic acid water-based polymer binder
Through the development of amidated polyacrylic acid aqueous polymer binder, the amidation reaction of levodopa and polyacrylic acid and in-situ crosslinking of glycerol are used to form a three-dimensional network structure, which solves the structural disintegration of the silicon-based negative electrode due to volume expansion. and the problem of shortening cycle life, achieving higher cycle stability and energy density.
Patent Information
- Application Number
- CN202411362335.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The silicon-based anode has caused structural disintegration and shortened cycle life in lithium-ion batteries due to volume expansion, and traditional binders cannot effectively solve these problems.
A amidated polyacrylic acid aqueous polymer binder was developed to form a three-dimensional network structure with dynamic repair ability and strong mechanical properties through the amidation reaction of levodopa and polyacrylic backbone, combining with glycerol.
The cycle stability and energy density of the silicon-based negative electrode are significantly improved, effectively suppressing the volume expansion of the SiOx negative electrode during the charging and discharging process, and extending the cycle life of the battery.
Smart Images

Figure CN119463748A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and more specifically, relates to an amide polyacrylic acid aqueous polymer binder for silicon-based anodes of lithium-ion batteries, its preparation method and application. Technical Background
[0002] In recent years, with the increasing prominence of the common problems of range anxiety in electric vehicles and insufficient battery power in portable electronic devices, the market has put forward an urgent demand for lithium-ion battery technology that pursues higher energy density, longer cycle life, and optimized economic costs. Traditional lithium-ion battery anodes mostly use graphite materials, but their limited theoretical specific capacity (370 mAh g -1 ) has become a bottleneck restricting the further improvement of their performance. Silicon-based materials, with their excellent specific capacity (up to 4200 mAh g -1 ), low working potential, and abundant natural resource reserves, are regarded as one of the key candidates to drive the innovation of lithium-ion battery technology.
[0003] Currently, silicon anodes face severe challenges in practical applications: the huge volume change (about 400%) during charge and discharge leads to particle fragmentation, electrode structure disintegration, and electrical contact failure, seriously hindering their commercialization process. In addition, the instability of the solid electrolyte interface (SEI) caused by the repeated insertion and extraction of lithium ions further shortens the cycle life of the battery. To solve these problems, the scientific research community has turned its attention to composite silicon materials such as SiO x (0 < x < 2). Although they have improved in cycle stability, they are still limited by significant volume changes (100 - 200%), resulting in rapid battery capacity decay and poor rate performance. To effectively alleviate the volume expansion problem of silicon-based materials, researchers have continuously explored new strategies, such as nanostructure design, surface modification, and the development of high-performance binders. Among them, the binder, as a bridge connecting the active material and the conductive network, is crucial for maintaining the integrity and mechanical properties of the electrode structure. Traditional binders such as polyvinylidene fluoride (PVDF) are difficult to meet the strict requirements of silicon-based anodes due to their weak binding force caused by their molecular structure characteristics, high cost, and low environmental friendliness.
[0004] In recent years, the research in this field has advanced rapidly, opening up new paths for the development of silicon-based anodes and even the entire lithium-ion battery technology. Developing new multifunctional binders, aiming to simplify the synthesis process, improve environmental friendliness and cost-effectiveness, while enhancing the adaptability to the volume expansion of silicon-based materials, has become a research hotspot. These new binders not only need to have strong binding ability to resist mechanical stress, but also need to maintain the stability of the electrode structure, thus improving the overall electrochemical performance of lithium-ion batteries. Summary of the Invention
[0005] In order to solve the above-mentioned deficiencies and disadvantages of the prior art, the present invention aims to provide an amidated polyacrylic acid aqueous polymer binder for lithium-ion battery silicon-based negative electrode, which forms a three-dimensional network structure with dynamic repair ability and strong mechanical properties through the amidation reaction of levodopa and the polyacrylic acid main chain combined with in-situ crosslinking of glycerol, significantly improves the cycle stability and energy density of the silicon-based negative electrode, and can effectively inhibit SiO x The volume expansion of the negative electrode during the charge and discharge process increases the SiO x Cycling stability of the negative electrode.
[0006] Another object of the present invention is to provide a method for preparing the amidated polyacrylic acid water-based polymer binder.
[0007] Another object of the present invention is to provide application of the amidated polyacrylic acid water-based polymer binder.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] The invention discloses an amidated polyacrylic acid aqueous binder for a silicon-based negative electrode of a lithium-ion battery. The aqueous binder is abbreviated as PLG. The polyacrylic acid is dissolved in a phosphate buffer solution, a NaOH solution is added to adjust the pH value of the polyacrylic acid solution to 5-6, 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, N-hydroxysuccinimide and levodopa are added in sequence under a protective atmosphere, stirred to react fully, dialyzed and freeze-dried to obtain a preliminary product PL, and then PL is uniformly mixed with glycerol to obtain the product.
[0010] Preferably, the mass ratio of the polyacrylic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and levodopa is (5-10):(1-2):(0.6-1.2):1; the mass ratio of the polyacrylic acid and phosphate buffer solution is 1:(140-160); the mass ratio of the glycerol and PL is (0.2-0.4):1.
[0011] Preferably, the concentration of the NaOH solution is 5-8 mol / L; and the protective atmosphere is nitrogen, argon, helium or neon.
[0012] Preferably, the dialysis time is 2 to 3 days, the freeze-drying temperature is -50 to -70°C, and the freeze-drying time is 2 to 3 days.
[0013] Preferably, the phosphate buffer solution is sodium dihydrogen phosphate, disodium hydrogen phosphate and deionized water in a mass ratio of (10-11):(1.5-2):1000, and the pH of the phosphate buffer solution is 5-7.
[0014] The method for preparing the amidated polyacrylic acid aqueous polymer binder for the silicon-based negative electrode of a lithium-ion battery comprises the following steps:
[0015] S1. dissolving polyacrylic acid in a phosphate buffer solution, adding a NaOH solution to adjust the pH of the solution to 5-6, then adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and stirring thoroughly until dissolved, adjusting the pH to 5-6 again, then adding N-hydroxysuccinimide, and continuing to stir until completely dissolved;
[0016] S2. Under a protective atmosphere, levodopa was added to the above solution and stirred for 12 to 24 hours to fully react. After the reaction was completed, the solution was dialyzed and freeze-dried to obtain a preliminary product PL;
[0017] S3. Mix PL and glycerol and stir until they are uniform, to obtain an amidated polyacrylic acid aqueous binder, abbreviated as PLG binder.
[0018] The application of the amidated polyacrylic acid water-based polymer binder in lithium-ion batteries.
[0019] Preferably, the negative electrode material of the lithium ion battery is SiO x , 0 <x<2。
[0020] The application method of the binder of the present invention is as follows: the active material SiO x , the conductive agent Super P (conductive carbon black) and the binder are mixed in a mass ratio of (7-8): (2-1): 1, and after adding an appropriate amount of deionized water, they are placed in a degassing machine and stirred for 20-30 minutes to obtain a uniformly dispersed slurry. The obtained slurry is coated on a copper foil, first vacuum dried at 150°C for 2 hours, then vacuum dried at 80°C for 10 hours, and then cut into circular pole pieces with a diameter of 14 mm. The dried pole pieces are transferred to an argon-filled glove box for battery assembly. Among them, the lithium sheet in the battery is used as the counter electrode, the electrolyte uses 1 mol / L LiPF6 as the solute, ethylene carbonate (EC) and diethyl carbonate (DEC) with a volume ratio of 1:1 as the solvent, 10wt% fluoroethylene carbonate (FEC) and 1wt% ethylene carbonate (VC) as additives, and CR2032 button batteries are used for assembly.
[0021] The aqueous polymer binder of the present invention uses rigid polyacrylic acid as the main chain, introduces L-dopa molecules through an amidation reaction, and uses the catechol group in L-dopa to form a dynamic bond, that is, it can be reversibly reconstructed after breaking, and combined with the rich carboxyl groups of polyacrylic acid, the binder is endowed with the ability to easily reversibly reconstruct after breaking, thereby giving the electrode rapid self-healing ability and effectively alleviating the volume change of the silicon negative electrode. The lone pair of electrons of the nitrogen atom can form Li + Coordination bond, improve Li +The transport efficiency in the electrode is improved, thus improving the battery performance. Then, it is in situ cross-linked with glycerol, and a large number of hydroxyl and carboxyl cross-linking binders are cross-linked with SiO x It has abundant contact sites, thus forming a three-dimensional network of strong electrodes with strong mechanical properties, effectively releasing adverse stress, enabling the binder to better withstand the volume change during the charge and discharge process of the electrode, and contributing to the structural integrity of the electrode during the cycle, thereby improving the SiO x Negative electrode cycling stability.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. SiO of the present invention x The negative electrode binder is based on the dynamic bonds of catechol and the rich carboxyl groups of polyacrylic acid, which can be reversibly reconstructed after breaking, giving the electrode rapid self-healing ability. When the silicon-based negative electrode undergoes volume changes during the charge and discharge process, resulting in microcracks in the electrode material, this self-healing ability can effectively repair these cracks and prevent further pulverization and shedding of the electrode material.
[0024] 2. SiO of the present invention x The negative electrode binder is formed by the condensation of the amino group of L-dopa and the carboxyl group of polyacrylic acid to form an amide bond. The formation of this chemical bond enhances the adhesion between the binder and the silicon particles, allowing the binder to adhere more effectively to the surface of the silicon particles and prevent the silicon particles from falling off during the charge and discharge process. Through the amidation reaction, the combination of L-dopa and polyacrylic acid is more tightly, making the entire binder molecular structure more stable, which helps the binder maintain its performance in the battery working environment and is not prone to degradation or failure.
[0025] 3. SiO of the present invention x The nitrogen atom of the L-DOPA molecule in the negative electrode binder contains a lone pair of electrons, which can react with Li + Forming coordination bonds helps improve Li + The transport efficiency in the electrode reduces the internal resistance of the battery and improves the performance of the battery. After further in-situ cross-linking with glycerol, a tighter three-dimensional network structure is formed between the binder molecules, giving it stronger mechanical properties and better resistance to the stress caused by the volume change of the silicon-based negative electrode during the charging and discharging process. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The wave numbers of L-Dopa, PAA, PL, and PLG in Example 1 are between 2000 and 1000 cm -1 Fourier infrared spectrum at ;
[0027] Figure 2The wave number of L-Dopa, PAA and PL in Example 1 is between 4000 and 2000 cm -1 Fourier infrared spectrum at ;
[0028] Figure 3 The rate performance diagram of the button cell prepared in Application Example 1;
[0029] Figure 4 For application example 1 at 500mAg -1 Comparison of the cycle performance of button cells prepared in Example 1 under current density. DETAILED DESCRIPTION
[0030] The content of the present invention is further described below in conjunction with specific examples, but it should not be construed as limiting the present invention. If not specifically indicated, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0031] The molecular weight of the polyacrylic acid used in the embodiment of the present invention is 450,000; the purity of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is >98%; the purity of N-hydroxysuccinimide is >99%; the purity of levodopa is >99%; the purity of glycerol is >99% (ACS, analytical reagent in accordance with the American Chemical Association).
[0032] Example 1
[0033] 1. 0.5 g of polyacrylic acid (PAA) powder was dissolved in 70 g of phosphate buffer solution (10.5 g of sodium dihydrogen phosphate, 1.7 g of sodium dihydrogen phosphate and 1000 mL of deionized water, pH = 6), and the pH of the polyacrylic acid solution was adjusted to 5.5 with 5 mol / L NaOH solution. 191 mg of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride was added to activate the carboxylic acid part of the hydrated polymer, and after stirring for 30 min to completely activate the carboxyl group of polyacrylic acid, 115 mg of N-hydroxysuccinimide was added. After stirring at room temperature for 30 min, 0.1 g of levodopa (L-Dopa) was added, and the pH was adjusted to 6 with 5 mol / L NaOH solution. The reaction mixture was stirred at room temperature for 24 h, then dialyzed in a 10 kDa dialysis tube for 2 d, and freeze-dried at -70 ° C for 2 d to obtain the preliminary product PL.
[0034] 2. 0.4 g of PL was mixed with 0.16 g of glycerol and stirred until uniform to obtain an amidated polyacrylic acid aqueous polymer binder, abbreviated as PLG binder.
[0035] Figure 1The wave numbers of L-Dopa, PAA, PL, and PLG in Example 1 are between 2000 and 1000 cm -1 Fourier infrared spectrum at Figure 1 It can be seen that PAA is at 1700cm -1 There is a bending vibration peak of the carbonyl group in the carboxyl group (-COOH) at 1652 cm -1 The NH2 bending vibration peak is shown at 1700 cm-1. After the grafting reaction, both peaks are red-shifted to the wavenumber range of the carbonyl group of the amide group and the secondary amine, respectively, indicating that an amidation reaction occurred between the carboxyl group of PAA and the amino group of L-Dopa. The C=O stretching vibration peak of the carboxylic acid group of PAA is usually located at 1700 cm-1. -1 The position of the C=O stretching vibration peak of PLG is obviously blue-shifted to about 1716cm -1 , indicating the formation of a stronger hydrogen bond cross-linking structure. Figure 2 The wave number of L-Dopa, PAA and PL in Example 1 is between 4000 and 2000 cm -1 Fourier infrared spectrum at Figure 2 It can be seen that the original NH2 double peak vibration of L-Dopa (located at 3202cm -1 and 3397cm -1 ) disappeared in the grafted product, and the NH stretching vibration peak appeared, indicating that the NH2 group participated in the reaction and was converted into a new functional group during the grafting process. At the same time, PAA did not have a vibration peak in the corresponding area because it did not contain an amine group, further confirming the specificity of the grafting reaction.
[0036] Example 2
[0037] 1. Dissolve 1 g of polyacrylic acid (PAA) powder in 70 g of phosphate buffer solution (10.5 g of sodium dihydrogen phosphate, 1.7 g of sodium dihydrogen phosphate and 1000 mL of deionized water, pH = 6), and adjust the pH of the polyacrylic acid solution to 6 with a 6 mol / L NaOH solution. Add 191 mg of 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride to activate the carboxylic acid portion of the hydrated polymer, stir for 30 min to fully activate the carboxyl group of polyacrylic acid, and then add 115 mg of N-hydroxysuccinimide. After stirring at room temperature for 30 min, add 0.1 g of levodopa (L-Dopa), and adjust the pH to 6 with a 6 mol / L NaOH solution. The reaction mixture was stirred at room temperature for 24 h, then dialyzed in a 10 kDa dialysis tube for 2 d, and freeze-dried at -70 ° C for 2 d to obtain the preliminary product PL.
[0038] 2. 0.8 g of PL was mixed with 0.16 g of glycerol and stirred until uniform to obtain an amidated polyacrylic acid aqueous polymer binder, abbreviated as PLG binder.
[0039] Application Example 1
[0040] The active material SiO x , the conductive agent SuperP is mixed with the aqueous polymer binder PLG of Example 1, 600-800 mL of deionized water is added, and the mixture is placed in a degassing machine and stirred for 20-30 min to obtain a uniformly dispersed slurry. The obtained slurry is coated on a copper foil, first vacuum dried at 150°C for 2 h, then vacuum dried at 80°C for 10 h, and then cut into a circular pole piece with a diameter of 14 mm. The pole piece is transferred to an argon-filled glove box for battery assembly. The lithium sheet in the battery is used as the counter electrode, the electrolyte uses 1 mol / L LiPF6 as the solute, ethylene carbonate (EC) and diethyl carbonate (DEC) with a volume ratio of 1:1 as the solvent, 10 wt% fluoroethylene carbonate (FEC) and 1 wt% ethylene carbonate (VC) as additives, and CR2032 button batteries are used for assembly.
[0041] Figure 3 This is the rate performance diagram of the button cell prepared in Application Example 1. Figure 3 It can be seen that SiO x @PLG negative electrode at current density of 0.2A -1 , 0.5Ag -1 , 1Ag -1 , 2Ag -1 The reversible capacities are 1378.4 mAh g -1 , 1186.53mAh g -1 、937.36mAh g -1 and 686.05mAh g -1 When the current density is adjusted to 0.2Ag -1 When -1 This indicates that the SiOx@PLG negative electrode has good structural stability and reversibility, can maintain a high capacity at different charge and discharge rates, and can quickly recover its performance after the charge and discharge rate changes.
[0042] Comparative Example 1
[0043] 1. Add 0.55 g of polyacrylic acid powder to 10 g of deionized water and stir in a magnetic stirring channel until it is completely dissolved to obtain a polyacrylic acid binder.
[0044] 2. Mix the active material SiO with a mass ratio of 7:2:1 x, the conductive agent SuperP is mixed with the polyacrylic acid binder, 600-800 mL of deionized water is added, and the mixture is placed in a degassing machine and stirred for 20-30 min to obtain a uniformly dispersed electrode slurry. The electrode slurry is applied to the copper foil, first vacuum dried at 150°C for 2 h, then vacuum dried at 80°C for 10 h, and then cut into circular electrodes with a diameter of 14 mm.
[0045] 3. The electrode was transferred to an argon-filled glove box for battery assembly. The lithium sheet in the battery was used as the counter electrode, the electrolyte was 1 mol / L LiPF6 as the solute, ethylene carbonate (EC) and diethyl carbonate (DEC) with a volume ratio of 1:1 as the solvent, 10 wt% fluoroethylene carbonate (FEC) and 1 wt% ethylene carbonate (VC) as additives, and CR2032 button cells were used for assembly.
[0046] The button cells assembled in Application Example 1 and Comparative Example 1 were left at 28°C for 10 hours, and the electrochemical performance was tested by constant current in the Xinwei test system. The test conditions were: current density 500mAg -1 ; Voltage window 0.1~1.5V. Figure 4 For application example 1 at 500mAg -1 Comparison of the cycle performance of the button cell prepared in Example 1 under current density, by Figure 4 It can be seen that the button cell prepared in Comparative Example 1 has a -1 At this current density, the capacity decays to 908.12 mAh g after 100 cycles. -1 , SiO2 prepared from the amidated aqueous polymer binder (PLG) of Example 1 x Negative electrode at 500mAg -1 At the current density, the first discharge capacity is 2171.61 mAh g -1 After 100 cycles, the cycle retention rate was 87.35%, and the capacity was still maintained at 1170.55 mAh g -1 The results show that SiO x The PLG negative electrode exhibits excellent cycle stability, and the amidated polyacrylic acid aqueous polymer binder can effectively inhibit the SiO2 x The volume expansion of the negative electrode material makes SiO x The negative electrode exhibits good cycling stability.
[0047] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. An amidated polyacrylic acid aqueous binder for a silicon-based negative electrode of a lithium-ion battery, characterized in that: The aqueous binder is abbreviated as PLG, which is prepared by dissolving polyacrylic acid in a phosphate buffer solution, adding a NaOH solution to adjust the pH of the polyacrylic acid solution to 5-6, and adding 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, N-hydroxysuccinimide and levodopa in sequence under a protective atmosphere, stirring to fully react, dialyzing and freeze-drying to obtain a preliminary product PL, and then mixing PL with glycerol to obtain the product.
2. The amidated polyacrylic acid aqueous polymer binder for lithium ion battery silicon-based negative electrode according to claim 1, characterized in that: The mass ratio of the polyacrylic acid, 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride, N-hydroxysuccinimide and levodopa is (5-10):(1-2):(0.6-1.2):1; the mass ratio of the polyacrylic acid and phosphate buffer solution is 1:(140-160); the mass ratio of the glycerol and PL is (0.2-0.4):
1.
3. The amidated polyacrylic acid aqueous polymer binder for lithium ion battery silicon-based negative electrode according to claim 1, characterized in that: The concentration of the NaOH solution is 5-8 mol / L; the protective atmosphere is nitrogen, argon, helium or neon.
4. The amidated polyacrylic acid aqueous polymer binder for lithium ion battery silicon-based negative electrode according to claim 1, characterized in that: The dialysis time is 2 to 3 days, the freeze-drying temperature is -50 to -70°C, and the freeze-drying time is 2 to 3 days.
5. The amidated polyacrylic acid aqueous polymer binder for lithium ion battery silicon-based negative electrode according to claim 1, characterized in that: The phosphate buffer solution is sodium dihydrogen phosphate, disodium hydrogen phosphate and deionized water in a mass ratio of (10-11):(1.5-2):1000, and the pH value of the phosphate buffer solution is 5-7.
6. The method for preparing the amidated polyacrylic acid aqueous polymer binder for silicon-based negative electrode of lithium ion battery according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. dissolving polyacrylic acid in a phosphate buffer solution, adding a NaOH solution to adjust the pH of the solution to 5-6, then adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and stirring thoroughly until dissolved, adjusting the pH to 5-6 again, then adding N-hydroxysuccinimide, and continuing to stir until completely dissolved; S2. Under a protective atmosphere, levodopa was added to the above solution and stirred for 12 to 24 hours for sufficient reaction. After the reaction was completed, the solution was dialyzed and freeze-dried to obtain a preliminary product PL; S3. Mix PL and glycerol and stir until they are uniform, to obtain an amidated polyacrylic acid aqueous binder, abbreviated as PLG binder.
7. Use of the amidated polyacrylic acid aqueous polymer binder according to any one of claims 1 to 5 in lithium ion batteries.
8. Use of the amidated polyacrylic acid aqueous polymer binder in lithium ion batteries according to claim 7, characterized in that: The negative electrode material of the lithium ion battery is SiO x , 0 <x<2。
Citation Information
Patent Citations
Lithium ion battery negative electrode binder and preparation method of lithium ion battery negative electrode
CN110350195A
Modification method and application of silicon-based binder for negative electrode material of lithium ion battery
CN112322223A
Thiolated polyacrylic acid water-based polymer binder for silicon-based negative electrode of lithium ion battery as well as preparation method and application of thiolated polyacrylic acid water-based polymer binder
CN116759581A
Amphiphilic binder for silicon-carbon negative electrode of lithium ion battery as well as preparation method and application of amphiphilic binder
CN116874647A
Method for improving electrochemical performance of sodium ion battery negative electrode material
CN117673363A
Cited By
Preparation method and application of dopamine functionalized polyacrylic acid bionic binder
CN120904817A
Ternary composition for dispersing conductive agent, aqueous carbon nanotube conductive agent dispersion liquid and preparation method and application of aqueous carbon nanotube conductive agent dispersion liquid
CN121097082A
Graphene-coated lithium ion battery negative electrode material and preparation method thereof
CN121565837A